The Gulf : the making of an American sea - Davis, Jack E., 1956- (Liveright Publishing Corporation, 2017)
Significant beyond tragic oil spills and hurricanes, the Gulf has historically been one of the world's most bounteous marine environments, supporting human life for millennia. Based on the premise that nature lies at the center of human existence, Davis takes readers on a compelling and, at times, wrenching journey from the Florida Keys to the Texas Rio Grande, along marshy shorelines and majestic estuarine bays, both beautiful and life-giving, though fated to exploitation by esurient oil men and real-estate developers. David shares previously untold stories, parading a vast array of historical characters past our view: sports-fishermen, presidents, Hollywood executives, New England fishers, the Tabasco king, a Texas shrimper, and a New York architect who caught the "big one". Sensitive to the imminent effects of climate change, and to the difficult task of rectifying the assaults of recent centuries, this book suggests how a penetrating examination of a single region's history can inform the country's path ahead. --